Effectiveness of an Educational Program on Type 2 Diabetic Patients' Knowledge Regarding Risk Factors of Diabetic Foot - Shahad Sabah Khudhair, Sabah Abbas Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes is a group of metabolic disorders characterized by high blood sugar caused by defects in insulin secretion, action, or both Objectives: Evaluate effectiveness of educational program on type 2 diabetic patients’ knowledge regarding Risk Factors of Diabetic Foot .Find out the relationship between of type 2 diabetic patients’ knowledge regarding Risk Factors of Diabetic Foot Methodology: quasi-experimental (one control group and one study group) design study, has been utilized for the current study. Study carried out in Imam AL-Hussein Medical-City. A non –probability (purposive) sample of (60) adult patients who are diagnosed with type2 diabetes mellitus these patients have met the study criteria and they are divided into two groups, (30) patients are assigned to a study group was exposed to the educational program, and (30) patients as a control group was not exposed to the educational program. Results: Result show that mean of score of Knowledge item in Pre-test (MS=1.31) in study group, and (MS=1.32) in control group. After application Program (Post-test) study group Knowledge improve to become (MS=1.85) , While control group knowledge still (MS=1.31).Conclusions: Applied educational program effectively improved the level of knowledge of the study group participants based on the findings of the study Conclusion: The results of the needs assessment show that the level of knowledge about the risk factors for the diabetic foot of the patients was low.